2018
DOI: 10.1080/00071668.2018.1423676
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lysolecithin supplementation in low-energy diets on growth performance, nutrient digestibility, viscosity and intestinal morphology of broilers

Abstract: 1. The study aimed to investigate the effect of lysolecithin supplementation in low-energy diets on growth, nutrient digestibility and intestinal mucosa characteristics of broilers. 2. A total of 800 one-d-old Ross 308 broiler chickens were assigned to 4 dietary treatments consisting of 10 replicates of 20 broilers each. Broilers were fed with 4 different diets: (i) HE: positive control group broilers received a diet with unaltered energy; (ii) LE: negative control group broilers received a diet with lower ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
6
21
1
Order By: Relevance
“…Although low intake increases digestibility, in present study this mechanism is failed due to high fat content in HE diet (Lammasak et al, 2019). Our findings are similar with the findings of Dairo et al (2010) and Papadopoulos et al (2018) who reported that LE or HE diet did not have any effect on fat digestibility. Similarly, Hu et al (2018) reported that supplementing 0.015% lipase enzyme in LE diet had similar fat digestibility compared to HE diets.…”
Section: Effects Of Bile Acids and Lipase Supplementation In Low-enersupporting
confidence: 92%
“…Although low intake increases digestibility, in present study this mechanism is failed due to high fat content in HE diet (Lammasak et al, 2019). Our findings are similar with the findings of Dairo et al (2010) and Papadopoulos et al (2018) who reported that LE or HE diet did not have any effect on fat digestibility. Similarly, Hu et al (2018) reported that supplementing 0.015% lipase enzyme in LE diet had similar fat digestibility compared to HE diets.…”
Section: Effects Of Bile Acids and Lipase Supplementation In Low-enersupporting
confidence: 92%
“…According to previous researches, the WG of channel catfish in the same life stage of present study (body weight about 14.77 g) was 161%-489% after the 10 weeks feeding trial (Gatlin & Bai, 1993;Lochmann, Islam, Phillips, Adam, & Everette, 2012;Nguyen & Davis, 2016;Peterson, Booth, & Manning, 2012;Pohlenz et al, 2012;Rábago-Castro, Sanchez, Pérez-Castañeda, & González-González, 2006 (Brautigan et al, 2017;Li et al, 2018Li et al, , 2010Melegy, Khaled, El-Bana, & Abdellatif, 2010;Papadopoulos et al, 2018;Wang et al, 2009). However, Wang et al…”
Section: Discussionsupporting
confidence: 67%
“…Improvements of feed utilization by dietary lysolecithin supplementation were also found in previous studies in broilers, common carp Cyprinus carpio var. Jian, crucian carp Carassais auratus gibelio and turbot Scophthalmus maximus L. (Brautigan et al, ; Li et al, , ; Melegy, Khaled, El‐Bana, & Abdellatif, ; Papadopoulos et al, ; Wang et al, ). However, Wang et al () and Li et al () reported that dietary addition of lysolecithin resulted in a significant increase in WG of common carp and turbot, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in reformulated diets, where the aim of supplementation was to recover the reduction in energy between the standard control and the reformulated diet by lysolecithin supplementation, there were no significant effects of treatment on growth performance. These results agree with the findings of Papadopoulos et al (2018), who found that supplementation with 250 g/t LCL in feed could maintain broiler performance in diets that had been reduced by 64.5 kcal ME/kga similar energy reduction to the average applied in this analysis' constituent trials. Chen et al (2019) found that there were significant growth responses to supplemental LCL at 250, 500 and 750 g/t, but the results did not show a clear linear dose response.…”
Section: Discussionsupporting
confidence: 92%